Acceptability of Cervical and Anal HPV Self-sampling in a Sample of Hispanic Women in Puerto Rico - Ortiz, Ana P.; Alejandro, Natalia; Pérez, Cynthia M.; Otero, Yomayra; Soto-Salgado, Marievelisse; Palefsky, Joel M.; Tortolero-Luna, Guillermo; Romaguera, Josefina (Puerto Rico Health Sciences Journal, 2012)
Self-sampling techniques have been shown to be reliable in determining human papillomavirus (HPV) infection, although the acceptability of this method of sampling has not been studied in Puerto Rico (PR). The objective of this study was to determine the acceptability of cervicovaginal and anal self-sampling for HPV DNA testing among women in PR. One hundred women aged 18-34 years old and undergoing routine Pap smears in an OBGYN clinic in PR were recruited. Interviewer-administered and computer-based questionnaires were used to collect information on relevant risk factors. To assess acceptability, four-item acceptability Likert scales were used that measured comfort, pain, privacy, and embarrassment. Overall acceptability indexes were calculated as the sum of the Likert scores. Clinician-collected and selfcollected cervicovaginal and anal samples for HPV-DNA testing were obtained from the participating women. Although the acceptability of both sampling methods was high, it was higher for self- rather than clinician-sampling of the cervix (difference in mean score = -0.71, p < 0.05); contrarily, it was higher for clinician-sampling of the anus (difference in mean score = 0.64). When analyzing individual items within the scale, less embarrassment was observed with respect to the self-collection of cervical and anal samples. Nevertheless, most women reported that they preferred having a clinician collect cervical and anal samples (67% and 61%, respectively); and most of these women (86% for cervical samples and 92% for anal samples) felt more confident that this sample would be properly taken. Despite this, in this population, the high level of acceptability with regard to self-collected samples and the previously documented concordance between self- and clinician-collected samples support the use of cervical and anal HPV DNA self-sampling techniques in future HPV-related population-based studies and screening programs in PR.